A radial decrease in kinetic temperature measured with H2CO in 30 Doradus - Indebetouw, Rémy; Wong, Tony; Madden, Suzanne; Sewiło, Marta; Roman-Duval, Julia; Chevance, Mélanie; Rubio, Monica (The astrophysical journal, 2024)
Feedback from star formation is a critical component of the evolution of galaxies and their interstellar medium. At parsec scales internal to molecular clouds, however, the observed signatures of that feedback on the physical properties of CO-emitting gas have often been weak or inconclusive. We present subparsec observations of H2CO in the 30 Doradus region, which contains the massive star cluster R136 that is clearly exerting feedback on its neighboring gas. H2CO provides a direct measure of gas kinetic temperature, and we find a trend of decreasing temperature with projected distance from R136 that may be indicative of gas heating by the stars. While it has been suggested that mechanical heating affects H2CO-measured temperature, we do not observe any correlation between T K and line width. The lack of an enhancement in mechanical feedback close to R136 is consistent with the absence of a radial trend in gravitational boundedness seen the Atacama Large Millimeter/submillimeter Array CO observations. Estimates of cosmic-ray flux in the region are quite uncertain, but can plausibly explain the observed temperatures if R136 itself is the dominant local source of energetic protons. The observations presented here are also consistent with the H2CO-emitting gas near R136 being dominated by direct radiation from R136 and photoelectric heating in the photodissociation regions.